Social Characteristics Of Speech Of Characters In Dramatic Works - Ismailov Jahangir Jaloliddinovich (Euro Asian Journal Publishing, 2024)
It is known that not every dialogue can create a dramatic work, but a dramatic dialogue is recognized for a play, which embodies the living image of characters, and can create action, not just any action, but a life-dramatic action consisting of a world of conflicts.
Keywords: Dramatic; play; monos composition; monologic discourse